PENGARUH KEBIJAKAN DIVIDEN, KONSERVATISME AKUNTANSI DAN INTENSITAS MODAL TERHADAP KUALITAS LABA (Studi Empiris pada Perusahan Properti dan Real Estate yang terdaftar di BEI pada tahun 2017-2021) - Magdalena Dikaluci (JURNAL PUNDI, 2023)
ABSTRACT This study aims to determine the effect of Dividend Policy, Accounting Conservatism and Capital Intensity simultaneously affect Earnings Quality, Dividend Policy influences Earnings Quality, Accounting Conservatism influences Earnings Quality and Capital Intensity influences Earnings Quality. This type of research is quantitative in nature and the data used is secondary data with the media in the form of financial statements of property and real estate companies taken from IDX. The population used in this study was 60 companies and 12 samples of property and real estate companies listed on the Indonesia Stock Exchange during the 2017-2021 period. Data management uses eviews 9 version. Based on the results of the tests conducted, simultaneously the Vivid Policy, Accounting Conservatism and Capital Intensity variables have an influence on Earnings Quality with a probability value (F- statistic) of 0.002247 <0.05 with a significance level of 0.05 (5%). Dividend policy affects the quality of earnings with a probability value of 0.0000<0.05. Accounting conservatism has no significant effect on earnings quality with a probability value of 0.5502> 0.05. Capital intensity has no significant effect on earnings quality with a probability value of 0.3569 <0.05.keywords: Dividend Policy, Accounting Conservatism and Capital Intensity on Earnings Quality